Impact assessment of wastewater on water quality using new quality indices and multiple linear regression - Florinela Pirvu; Iuliana Paun; Vasile Iancu; Nicoleta Vasilache; Daniel Rudaru; Marcela Niculescu; Anda Gabriela Tenea; Florentina Laura Chiriac (Romanian Journal of Ecology & Environmental Chemistry)
The Wastewater Quality Index (WWQI) is a unique measure that synthesizes the overall quality of wastewater. The main objective of the study was to evaluate whether the quality of wastewater reaching the treatment plant is suitable for optimal disposal using the WWQI approach. To understand the correlation between the determined indicators, Pearson correlation coefficients were calculated, so that the results of the analyses reflect the overall quality of the evaluated wastewater. Additionally, statistical analysis was employed to develop a simple prediction model through multiple linear regression (MLR) to predict WWQI based on various wastewater quality parameters. The results indicate good and regular quality of treated wastewater for safe disposal, according to the classification of WWQI levels, and the prediction model yielded values similar to those estimated.